Simulation of equilibrium and transport in advanced FRCS. (15th October 2021) - Dettrick, S.A.; Barnes, D.C.; Ceccherini, F.; Galeotti, L.; Galkin, S.A.; Gupta, S.; Hubbard, K.; Koshkarov, O.; Lau, C.K.; Mok, Y.; Necas, A.; Nicks, B.S.; et al.
Abstract: The advanced beam-driven FRC is a field reversed configuration (FRC) with the addition of neutral beam (NB) injection, electrode biasing, and magnetic expander divertors. The resulting configuration has novel features that make it necessary to revisit many key results in FRC theory. Three of these features include (i) a large energetic ion population, (ii) in-principle capability to adjust the electric field and rotation profiles, and (iii) a combination of magnetic and electrostatic confinement of electrons in the SOL. In some fueling scenarios the electron density profile may exhibit a significant peak outside of the separatrix. To explore these features a hybrid fluid/kinetic equilibrium model has been used to reconstruct typical experimental profiles of the C-2W experiment. Results indicate that the energetic ions provide at least 50% of the total plasma pressure. These equilibrium profiles have been used as initial conditions for global, cross-separatrix, turbulent transport simulations using the 3D electrostatic particle-in-cell code ANC. Electrostatic fluctuations were found to nonlinearly saturate at an amplitude which is an order magnitude lower than that observed previously. The tokamak turbulence code GTC code has also been extended to handle FRC physics in the new GTC-X version, which has been used to perform simulations of turbulent transport in the SOL relevant to electrode biasing. It is found that equilibrium E × B flow shear significantly decreases ion temperature gradient saturation amplitude and ion heat transport. Also in the SOL, a 1D2V continuum code has been developed and applied to parallel electron heat transport. Results show the formation of pre-sheath potential and reduction of parallel electron heat loss close to the ideal ambipolar limit, a result which has been validated by experimental diagnostics. These transport modifications caused by the three novel configuration features help to explain the remarkable plasma performance of the C-2W experiment.